Effects of massage therapy on preterm infants and their mothers: a systematic review and meta-analysis of randomized controlled trials - Zhang, Yu; Duan, Chunlan; Cheng, Luying; Li, Haihong (Frontiers in Pediatrics, 2023)
Background: Massage therapy for preterm newborns has received increasing attention in recent years due to its beneficial clinical outcomes. However, disagreements persisted in different investigations. Method: We performed a systematic literature search in the Cochrane Library, Embase, PubMed, Web Science, and CINAHL to retrieve randomized controlled trials of premature infants receiving massage therapy and their impact on maternal and infant outcomes. Outcomes were mother-infant attachment, and oxygen saturation, motor funtion, reflex, temperature, and calorie intake. The tool developed by the Cochrane collaboration assessed risk bias. With a 95% confidence interval (CI), the integration’s results were presented as mean difference or standardized mean difference. The registration number was CRD42022337849. Results: Of 940 records retrieved, 15 trials were included. Massage therapy increased oxygen saturation (SMD=2.00, 95%CI [1.17 to 2.83], P<0.0001). Massage therapy can strengthen mother-infant attachment(SMD=2.83, 95%CI [2.31 to 3.35], P<0.00001). Other outcomes, including motor activity, relaxation, caloric intake, and temperature, did not differ significantly. Conclusion: Massage therapy can significantly improve oxygen saturation and strengthen maternal-infant attachment. However, prior to making a recommendation, additional research with a larger sample size and more rigorous design should be conducted due to the heterogeneity of studies in several outcomes.